Managing development projects—The partnership between project managers and systems engineers. Issue 3 (18th November 2018) - Kordova, Sigal; Katz, Eyal; Frank, Moti
Abstract: There are two significant "players" in development projects: the project manager and the systems engineer, both working together in cooperation with the aim of carrying out technical (execution/performance, quality) and managerial (schedule, costs, and customer satisfaction) project goals. The goal of the current study is to identify the management processes shared by project managers and systems engineers in the defense industry, understand which factors influence how joint project management is accomplished and how it impacts meeting project goals, and provide recommendations for joint project management that will lead to project success. The research method was qualitative, based on 16 semistructured interviews with project managers and systems engineers in defense companies that deal with the development of technological systems. The main recommendations for joint project management are: clear distribution of responsibility and delegation of authority between the two professionals before starting the project; choosing a project manager who was once a systems engineer or who possesses engineering knowledge; insistence on an ongoing dialog between the two professionals and solving/preventing conflicts through discussion and persuasion; as well as expanding common ground between the project manager and systems engineers' areas of responsibility.